An??lise da variabilidade da frequ??ncia card??aca em pacientes bronquiect??sicos est??veis - Amaral, Tatiane Soares (2013)
Introduction: Bronchiectasis (BCQ) is a chronic and debilitating respiratory disease with extrapulmonary factors that suggest the presence of cardiovascular autonomic dysfunction, however, based in our knowledge, there are no studies assessing autonomic function of these patients. Objectives: To assess the autonomic function in patients with clinically stable BCQ and correlate them with pulmonary function indices, functional and aerobic capacity. Method: Parameters of cardiac autonomic regulation were studied, by heart rate variability (HRV) in 26 patients with BCQ, being compared with healthy individuals and contrasted with rates of lung, functional and physical capacity rates, respectively by spirometry, incremental shuttle walking test (ISWT) and maximal cardiopulmonary exercise test (CPET). Results: The patients showed significant reduction in the high frequency component (HF, n.u.) (38 ?? 14 vs 53 ?? 15, p= 0.02) and increased in low frequency (LF, n.u.) (61 ?? 13 vs 47 ?? 15, p= 0.02) and in the relationship between the two components (LF/HF) (p=0.02) compared to healthy. There was no correlation between HRV indices with functional and physical capacity. The component of HF was positively correlated with forced expiratory volume in first second (FEV1) and the ratio FEV1 / forced vital capacity (FVC) (r = 0.4 for both). While there was a negative and significant correlation between LF and LF / HF with FEV1 (r = 0.4 and 0.3 respectively) and the FEV1/FVC (r = 0.5 and 0.4 respectively). Conclusion: BCQ patients have worse cardiac autonomic regulation in relation to healthy subjects, and the reduction in lung function is correlated to autonomic dysfunction in these patients with increased activation of the sympathetic nervous system.